2002
DOI: 10.1002/app.10706
|View full text |Cite
|
Sign up to set email alerts
|

Influence of γ‐irradiation on poly(methyl methacrylate)

Abstract: Poly(methyl methacrylate) (PMMA) was ␥-irradiated (5-20 kGy) by a 137 Cs source at room temperature in air. The changes in the molecular structure attributed to ␥-irradiation were studied by mechanical testing (flexure and hardness), size-exclusion chromatography, differential scanning calorimetry, thermal gravimetric analysis, and both Fourier transform infrared and solution 13 C-NMR spectroscopy. Scanning electron microscopy was used to investigate the influence of the dose of ␥ rays on the fracture behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 53 publications
4
23
0
Order By: Relevance
“…This result agrees with literature reports on the effect of gamma radiation on PMMA matrix 12,17 . During PMMA irradiation, both electronic excitation and ionization processes produces excited atoms and ions which lead to the release of side groups like CH 3 OOC• and main chain scissions 12,14 .…”
Section: Radio-stabilizing Action Of Pbs-np In Pmmasupporting
confidence: 93%
See 4 more Smart Citations
“…This result agrees with literature reports on the effect of gamma radiation on PMMA matrix 12,17 . During PMMA irradiation, both electronic excitation and ionization processes produces excited atoms and ions which lead to the release of side groups like CH 3 OOC• and main chain scissions 12,14 .…”
Section: Radio-stabilizing Action Of Pbs-np In Pmmasupporting
confidence: 93%
“…This result agrees with literature reports on the effect of gamma radiation on PMMA matrix 12,17 . During PMMA irradiation, both electronic excitation and ionization processes produces excited atoms and ions which lead to the release of side groups like CH 3 OOC• and main chain scissions 12,14 . It was reported that initial side-chain scissions generate macro radicals that further undergo main chain scissions 12,19 and is the basic reason for the radiation-induced degradation of PMMA.…”
Section: Radio-stabilizing Action Of Pbs-np In Pmmasupporting
confidence: 93%
See 3 more Smart Citations